1996
DOI: 10.1172/jci118749
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of perforin in muscle-infiltrating T cells in polymyositis and dermatomyositis.

Abstract: Polymyositis (PM) and dermatomyositis (DM) are the prototypical inflammatory diseases of skeletal muscle. In PM, CD8 ϩ T cells invade and destroy muscle fibers, whereas humoral effector mechanisms prevail in DM. We studied the expression of the cytotoxic mediator perforin in inflammatory cells in PM and DM muscle by semiquantitative PCR, immunohistochemistry and confocal laser microscopy. Similar levels of perforin mRNA were expressed in PM and DM, and abundant perforin-expressing CD3 ϩ CD8 ϩ and CD3 ϩ CD4 ϩ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
142
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 37 publications
1
142
1
4
Order By: Relevance
“…Distinct from DM but consistent with lymphocytic infiltrates observed in PM, muscle‐invading CD8 + T cells stain positive for pore‐forming and cytolytic molecules such as perforin, granzyme A, and granulysin 46, 47, 48. It has been demonstrated that perforin‐polarization within endomysial CD8 + T cells occurs toward target myofibers indicative of immunosynapse formation and arguing strongly for a possible recognition of specific antigens presented via MHC class I expressing myofibers 49. In line with this, muscle fibers in IBM patients express co‐stimulatory molecules such as ICOS‐L, CD276, and BB1 on their surface 48, 50, 51…”
Section: Pathomechanisms In Ibmmentioning
confidence: 53%
See 1 more Smart Citation
“…Distinct from DM but consistent with lymphocytic infiltrates observed in PM, muscle‐invading CD8 + T cells stain positive for pore‐forming and cytolytic molecules such as perforin, granzyme A, and granulysin 46, 47, 48. It has been demonstrated that perforin‐polarization within endomysial CD8 + T cells occurs toward target myofibers indicative of immunosynapse formation and arguing strongly for a possible recognition of specific antigens presented via MHC class I expressing myofibers 49. In line with this, muscle fibers in IBM patients express co‐stimulatory molecules such as ICOS‐L, CD276, and BB1 on their surface 48, 50, 51…”
Section: Pathomechanisms In Ibmmentioning
confidence: 53%
“…Short‐telomer‐bearing CD8 + CD28 − T cells are thought to comprise a highly differentiated oligoclonal subset arising from chronic antigen exposure as hypothesized for IBM19, 49, 73, 74, 75, 76, 77 and several autoimmune conditions are accompanied by increased frequencies of CD8 + CD28 − T cells 78, 79, 80. Furthermore, muscle‐infiltrating CD8 + T cells in patients suffering from PM and DM have been reported to be mainly CD28 − 81.…”
Section: Pathomechanisms In Ibmmentioning
confidence: 99%
“…In PM and IBM there is an endomysial inflammatory infiltrate with a predominance of CD8+ T cells surrounding and invading MHC-I expressing myofibers [16]. These cells putatively induce cytotoxic myonecrosis through an interaction between antigen-presenting MHC-I molecules and co-stimulatory molecules on CD8+ cells [6,17,18]. The infiltrating cells in PM also include CD68+ macrophages and myeloid dendritic cells, which are thought to participate in the cytotoxic process [2,19], as well as apoptosis-resistant CD8+CD28−/−, CD4+ CD28−/−, cells which have been suggested may contribute to treatment resistance [20].…”
Section: Immunopathogenesis Of Inflammatory Myopathiesmentioning
confidence: 99%
“…In PM, CD8ϩ T lymphocytes surround, invade, and apparently destroy HLA class I-expressing muscle fibers (8)(9)(10)(11)(12). Typically, the inflammatory infiltrate contains putative effector CD8ϩ T cells, which make tight membrane contact with the muscle fiber, orient their cytotoxic granules toward the contact zone (13), and sometimes deeply invade into the HLA class I-positive target fiber (14). Bystander cells, which are not in direct contact with muscle fibers, are located in interstitial spaces.…”
mentioning
confidence: 99%